2014 IEEE International Conference on Mechatronics and Automation 2014
DOI: 10.1109/icma.2014.6885662
|View full text |Cite
|
Sign up to set email alerts
|

Application-oriented design of mechatronic drive trains

Abstract: The scope of this paper is to establish a method to analyze, design and test mechatronic drive trains based on the application requirements concerning efficiency and energy consumption. The considered drive train consists of frequency inverter, electric motor and gearbox. A standard three phase two-level inverter with two different machine control strategies (constant torque angle CTA and maximum torque per Ampere MTPA) and two different PWM logics (third harmonic injection method and space vector modulation) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A modular drivetrain is often defined as a configuration of individual mechatronic function modules, where each part of the mechatronic application is expressed as a module. Power electronics, electrical machines, and mechanical systems are in this case seen as individual modules [1,9]. The overall drivetrain consists of a combination of several modules, as proposed by [4,10].…”
Section: Modularitymentioning
confidence: 99%
See 2 more Smart Citations
“…A modular drivetrain is often defined as a configuration of individual mechatronic function modules, where each part of the mechatronic application is expressed as a module. Power electronics, electrical machines, and mechanical systems are in this case seen as individual modules [1,9]. The overall drivetrain consists of a combination of several modules, as proposed by [4,10].…”
Section: Modularitymentioning
confidence: 99%
“…The model can thus be rewritten as a three-inertia system, two modules, and a load, as illustrated in Figure 2. This simplification was carried out according to (1), and the approach is further validated in Section 2.2, where it is shown that the drivetrain indeed acts as a three-inertia system.…”
Section: Dynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation